Entre estilos, técnicas e iconografias: algumas reflexões sobre o retrato através das capas das revistas Alfa e Lola Magazine - Débora Veríssimo Costa (2014)
Since wen magazines were segmented to both feminine and masculine publics, we find editorial formulas adapted to specific languages and contexts. From 1936, for example, we can notice not only, the photoengraving as a crucial expression of magazines, but also, the presence of industries, such as cosmetics and cinematographic, directly corresponding to the feminine press. At the 70s the expansion of global models can be noticed in magazines from different nationalities, now adapted to this global formulas. Resulting from strategies that remark these decades, contemporary magazines, ALFA and LOLA, show us a particular iconographie adapted to its covers that elects the head and shoulders composition as a portrait language that remarks a great majority of magazines from the same segment. This research considered that the image of the human head is a medium between techniques and artistic styles, applied in ways and processes of representing the human figure through history. We design a study based on the funerary Egyptian art, going through the renaissance of 15th century, the invention of photography and the mass production, of 20th and 21st centuries, intended to investigate the possible adaptations of the portrait and its perpetuation through out history. Considering magazines covers as a possible gender of portrait, we intend to find a line that will take it, beyond the commercial portrait and an industrial product. The cover will be taken as a place of plural significations.